A new combined power and dual ejector refrigeration system using zeotropic mixtures with composition adjustable driven by geothermal resource: An exergoeconomic performance evaluation. (February 2023) - Mosaffa, A.H.
Highlights: A conventional zeotropic power/cooling cogeneration system is improved using the separator. A comparative study and an exergoeconomic analysis is carries out. The proposed system shows a good improvement compared to the conventional one. The optimum value of the exergy efficiency of the proposed system reaches to 29.8%. Also, an optimal value of 9.83 $/GJ is obtained for overall unit cost of products. Abstract: In this study, a novel geothermal-driven combined power and dual ejector refrigeration (CPDER) system using the zeotropic mixture as the working fluid with composition adjustable is presented, investigated, and assessed from an exergoeconomic viewpoint. The proposed system includes two ejector refrigeration subsystems connected in parallel mode. The zeotropic mixture is distributed into these subsystems through a vapor-liquid separator with various compositions. To represent the superiority of the proposed CPDER system compared to the conventional ones, a comprehensive parametric perusal is conducted. The results reveal that the mixture composition and outlet pressure of the turbine have the biggest impact on the total exergy destruction and the net power output, while the outlet temperature of the evaporator has the biggest effect on the refrigeration capacity. Furthermore, optimal operating condition is found through a tri-objective optimization process where energy efficiency, exergy efficiency, and overall unit cost of products are chosen as objective functions. The optimization results detect that for the proposed CPDER system, the energy efficiency and exergy efficiency improve by 6.0% and 11.9%, respectively. In this case, a decrement of 1.18 $/GJ (10.7%) is obtained in the overall unit cost of products compared to the conventional CPER system.